Diffractive photonic applications mediated by laser reduced graphene oxides - Wang Sicong (Institue of Optics and Electronics, Chinese Academy of Sciences, 2018)
Modification of reduced graphene oxide in a controllable manner provides a promising material platform for producing graphene based devices. Its fusion with direct laser writing methods has enabled cost-effective and scalable production for advanced applications based on tailored optical and electronic properties in the conductivity, the fluorescence and the refractive index during the reduction process. This mini-review summarizes the state-of-the-art status of the mechanisms of reduction of graphene oxides by direct laser writing techniques as well as appealing optical diffractive applications including planar lenses, information storage and holographic displays. Owing to its versatility and up-scalability, the laser reduction method holds enormous potentials for graphene based diffractive photonic devices with diverse functionalities.